DESAIN SUPPLIER SELECTION TANDAN BUAH SEGAR (TBS) INDUSTRI KELAPA SAWIT DI PT BORNEO INDAH MARJAYA DI KABUPATEN PASER KALIMANTAN TIMUR - Miftaul Hasanah; Abdul Wahib Muhaimin; Silvana Maulidah (Jurnal Penelitian Pendidikan IPA, 2024)
The research aims to identify the optimal strategy for selecting suppliers, analyse criteria priorities, and rank the best suppliers in PT X, Paser Regency. The research method uses quantitative approach with data collection through questionnaires based on the ANP (Analytical Network Process) model. The sample was determined using purposive sampling of three employees of PT X. The analysis was conducted in three stages: descriptive, ANP using super decision software, and TOPSIS to rank the FFB suppliers. The results on ANP showed that the design of selection of FFB suppliers in PT X is based on 5 criteria and 16 sub-criteria. Price criteria include payment method, low price, easy agreement, and price stability. The claim policy criteria include quick response, assistance, and warranty. Quality criteria involve technical conformity, quality consistency, and defect rate. Geographical location criteria consider climate, distance, road conditions, and delivery time. The delivery criterion prioritises the sub criteria of the accuracy of the number of deliveries. The conclusion from TOPSIS showed that the highest ranking of FFB suppliers is given to UD. Naila Naufal Jaya, superior on price, quality, delivery, geographic location, and warranty criteria.